A CONTINUUM MECHANICS MODEL FOR NORMAL FAULTING USING A STRAIN-RATE SOFTENING RHEOLOGY: IMPLICATIONS FOR THERMAL AND RHEOLOGICAL CONTROLS ON CONTINENTAL AND OCEANIC RIFTING - Behn M.D.; Lin J.; Zuber M.T. (My University, 2002)
We use a strain-rate-dependent visco-plastic rheology in a finite element model to investigate the effects of crustal rheology and thermal structure on the development of normal faults in 2-D extending lithosphere. Strain-rate softening in the brittle regime is used to simulate the rate-dependence of frictional strength observed in laboratory studies. Results of numerical experiments show that efficient strain-rate softening can result in localized zones of high strain rate, which develop in response to the rheology and boundary conditions and are not imposed a priori. We argue that these zones of localized shearing are analogous to faults and use the calculated deformation field to predict the preferred location of fault formation for a range of thermal and rheologic conditions. When no regional temperature gradient is imposed, deformation is predicted to be distributed between several sets of conjugate normal faults. However, in the presence of a horizontally varying temperature field, faulting is calculated to focus where the lithosphere is thinnest, forming rift-like topography. Model results predict that when crustal thickness is sufficiently small that no ductile layer is present in the lower crust, deformation is mantle-dominated and rift half-width is controlled primarily by the vertical geothermal gradient. In contrast, when crustal thickness is large enough that the stress accumulation in the upper crust becomes much greater than the stress accumulation in the upper mantle, deformation becomes crust-dominated and the calculated rift half-width is a function of both crustal rheology and the vertical geothermal gradient. This implies that deformation in the brittle upper crust does not behave independently of a strong upper mantle, even in situations where ductile flow occurs in the lower crust.
Keywords: RHEOLOGY; LITHOSPHERE; DEFORMATION; STRAIN; RIFTING